In vitro activity and rodent efficacy of clinafloxacin for bovine and swine respiratory disease - Sweeney, Michael T.; Quesnell, Rebecca; Tiwari, Raksha; LeMay, Mary; Watts, Jeffrey (Frontiers in Microbiology, 2013)
Clinafloxacin is a broad-spectrum fluoroquinolone that was originally developed and subsequently abandoned in the late 1990s as a human health antibiotic for respiratory diseases. The purpose of this study was to investigate the activity of clinafloxacin as a possible treatment for respiratory disease in cattle and pigs. MIC values were determined using CLSI recommended procedures with recent strains from the Zoetis culture collection. Rodent efficacy was determined in CD-1 mice infected systemically or intranasally with bovine M. haemolytica or P. multocida, or swine A. pleuropneumoniae, and administered clinafloxacin for determination of ED50s. The MIC90 values for clinafloxacin against bovine P. multocida, M. haemolytica, H. somni and M. bovis were 0.125, 0.5, 0.125 and 1 µg/ml, respectively, and the MIC90 values against swine P. multocida, A. pleuropneumoniae, S. suis, and M. hyopneumoniae were ≤0.03, ≤0.03, 0.125 and ≤0.008 µg/ml, respectively. Efficacy in mouse models showed average ED50s of 0.019 mg/kg/dose in the bovine M. haemolytica systemic infection model, 0.55 mg/kg in the bovine P. multocida intranasal lung challenge model, 0.08 mg/kg/dose in the bovine P. multocida systemic infection model, and 0.7 mg/kg/dose in the swine A. pleuropneumoniae systemic infection model. Clinafloxacin shows good in vitro activity and efficacy in mouse models and may be a novel treatment alternative for the treatment of respiratory disease in cattle and pigs.